“Uma bênção para a humanidade”. Densidade teológica das organizações e lutas populares - Aquino Júnior, Francisco de (Revista Eclesiástica Brasileira, 2018)
Pela primeira vez na história da Igreja um papa convida lideranças de movimentos populares de várias regiões do planeta para discutir os grandes problemas do mundo atual e as busca e perspectivas de superação desses problemas a partir dos pobres e das vítimas. E faz isso por estar convencido da importância sócio-espiritual desses movimentos no processo de transformação da sociedade segundo o Evangelho de Jesus Cristo. O artigo trata especificamente do caráter salvífico-espiritual das organizações e lutas populares a partir dos discursos do Papa Francisco nos três encontros mundiais com os movimentos populares. Abstract: For the first time in the history of the Church a Pope invites leaders of popular movements from various regions of the planet to discuss the great problems of today’s world and search for the perspectives of solution for these problems from the viewpoints of the poor and the victims. And he does this because he is convinced of the socio-spiritual relevance of these movements in the process of transformation of society according to Jesus Christ’s Gospel. The article deals specifically with the salvific-spiritual character of the popular organizations and struggles expressed in Pope Francisco’s speeches in the three world meetings he held with the popular movements. Keywords: Pape Francis; Popular movements; Salvation-spiritual cha- racter.